CHANGES IN THE MODERN HEALTHCARE SYSTEM IN THE REPUBLIC OF UZBEKISTAN - Kasimovna, Khasanova Nozima (Scientific Impulse, 2024)
This article describes the rebuild healthcare systems implemented in the Republic of Uzbekistan at the current stage.